Răspuns :
3×[3+4×(15+5×m):9]=69
[3+4×(15+5×m):9]=69:3
3+4×(15+5×m):9=23
4×(15+5×m):9=23-3
4×(15+5×m):9=20
(15+5×m):9=20:4
(15+5×m):9=5
15+5×m=5×9
15+5×m=45
5×m=45-15
5×m=30
m=30:5
m=6
[3+4×(15+5×m):9]=69:3
3+4×(15+5×m):9=23
4×(15+5×m):9=23-3
4×(15+5×m):9=20
(15+5×m):9=20:4
(15+5×m):9=5
15+5×m=5×9
15+5×m=45
5×m=45-15
5×m=30
m=30:5
m=6
3×[3+4×(15+5×m):9]=69
[3+4×(15+5×m):9]=69:3
3+4×(15+5×m):9=23
4×(15+5×m):9=23-3
4×(15+5×m):9=20
(15+5×m):9=20:4
(15+5×m):9=5
15+5×m=5×9
15+5×m=45
5×m=45-15
5×m=30
m=30:5
m=6
[3+4×(15+5×m):9]=69:3
3+4×(15+5×m):9=23
4×(15+5×m):9=23-3
4×(15+5×m):9=20
(15+5×m):9=20:4
(15+5×m):9=5
15+5×m=5×9
15+5×m=45
5×m=45-15
5×m=30
m=30:5
m=6